General construction of molybdenum-based compounds embedded in flexible 3D interconnected porous carbon nanofibers with protective porous shell for high-performance lithium-ion battery. (July 2021) - Zhou, Xing-hai; Gao, Yuan; Lyu, Li-hua; Liang, Yue-yao; Li, Zhen-huan
Abstract: The rational design of electrode architecture coupling with high specific capacity nanomaterials is highly desirable to build superior energy storage system. Herein, molybdenum-based compounds embedded in flexible 3D interconnected porous carbon nanofibers with protective porous carbon shell are constructed via a facile electro-blowing spinning technique using as free-standing lithium-ion battery (LIB) anodes. Such a well-designed architecture possesses large surface area, protective porous carbon shell and 3D interconnected porous structure. Moreover, various high specific capacity molybdenum-based compounds, including MoS2, MoO2 and MoN, can homogenously disperse within the fibers under different carbonization condition, especially, some of them are bridged to the fiber skeleton through a thin graphite carbon layer. The synergetic coupling effects benefited from the structural and material advantages are effective to provide more lithium-ion storage active sites, fast electrons/ions transfer pathways and good structural integrity. Using as free-standing anodes of LIB, the three fibrous anodes deliver an excellent electrochemical performance in terms of high specific capacity, superior rate capability and satisfied cycling stability. Extraordinarily, the well-designed architecture of fibrous anodes might open a new paradigm to boost the creation of high-performance electrodes for various energy storage devices. Graphical abstract: Image 1 Highlights: A general approach to construct Mo-based compounds embedded in carbon nanofiber matrix is developed. Protective porous shell and 3D interconnected porous structure is promising to maximize ion/electron transfer rate. The proposed architecture paved a way for the construction of advanced electrode material for LIB.